Profile of Brain Tumor Patients in 10 Hospitals in North Sumatera - Rambe, Aldy S.; Fitri, Aida; Tonam, Tonam (Sumatera Medical Journal, 2018)
Although brain tumors only 1.4% of all tumors, high fatality rate made these tumors need special attention. In North Sumatera, there is no data on brain tumors patients profile. Objective: To determine brain tumor patients’ profile in North Sumatera, Indonesia. Method: A descriptive hospital-based study with primary data which taken from September–December 2012. Result: Of 75 brain tumors patients surveyed in 10 hospitals in North Sumatera 38 (50.7%) patients were male and 37 (49.3%) patients were female. Mean of age was 51.45 (11–87) years old. Most of the subjects were housewifes, 26 (34.7%) patients. The most common cause that brought these patients to see doctors was headache 32 (42.7%), followed by decreased level of consciousness 17 (22.7%). Clinical manifestations found in these patients were headache 67 (89.3%), dizziness/vertigo 41 (54.7%), convulsion 22 (29.3%), vomitting 32 (42.7%), motor dysfunction 46 (61.3%), sensory dysfunction 21 (28%), and cognitive decline 21 (28%). Only 7 patients (9.3%) had history of tumor in his/her relatives. Eighteen patients (24%) were treated surgically and 8 (10.7%) were given radiotherapy. 71 patients were alive (94.7%) when discharged from the hospitals due to various reasons. Head CT Scan/MRI showed primary tumors in 56 (74.7%) patients. Of these primary tumors 25 (44.6%) patients were meningioma and 19 (33.9%) were astrocytoma. Of 19 (25.3%) patients with secondary tumor, most common primary tumor where found in the lung 11 (57.9%). Conclusion: Sex the patients were equally distributed with mean of age was 51.45 (11–87) years old. The most common cause that brought these patients to seek for treatment were headache. Most of these patients were treated conservatively. The most common head CT Scan/MRI findings showed primary tumors.